In vitro Performance of Sweet Potato (Ipomoea batatus L.) in Bangladesh - Ahmed, Shamim; Yeasmin, Labony; Nazrul Islam, Mohammad (International Journal of Bio-resource and Stress Management, 2011)
A study was conducted to observe an in vitro performance of 10 sweet potato germplasms at the Tissue Culture Laboratory, Tuber Crops Research Centre, Bangladesh Agricultural Research Institute, Gazipur, Bangladesh during July to November, 2005. The explants of 10 sweet potato germplasms were cultured on MS media. Maximum 25% cultures developed shoot directly, though 90% cultures formed calli of which 70-85% developed complete microplants. Both development of direct shot and differentiation of callus occurred within 4-7 and 4-5 days, respectively, whereas it was 8-10 days for regeneration of microplant via callus. Within 35 days of culture period the microplants attained from 3.275 to 6.475 cm height and maximum number of 14.425 leaves and 3.825 roots microplants-1 were formed. Rooting of cultures occurred within 5-9 days in maximum 98% cultures and with 35 days culture period the maximum root length was 9.242 cm. The germplasms varied significantly for area of leaf in which maximum leaf area was 0.653 cm2. The germplasms had an internode length of 3.825-5.302 mm and; the maximum rate of node production and microplant growth rate were 2.885 nodes week-1 and 1.850 mm day-1, respectively.